PENGARUH KEGIATAN INTRAKURIKULER HADITS TERHADAP PRESTASI AKADEMIK SISWA DI SMA ISLAM ATTAUFIQ JAMBI - Noor Ikhsan Silviantoro; Bisri Tujang; Abd.Muthalib (CV. Adiba Aisha Amira, 2025)
This study examines the effect of extracurricular activities of Tahfidz Al-Qur'an on students' academic achievement at SMA Islam Attaufiq Jambi. This study uses a quantitative approach with a correlational design to determine the relationship between students' participation in Tahfidz activities and their academic achievement. Data collection methods include a questionnaire to assess the level of participation and documentation of academic records. Statistical analysis, including regression, showed a positive and significant correlation between Tahfidz participation and academic achievement, with the activity contributing 21% to academic results. This suggests that a structured religious program contributes to the holistic development of students, which includes a balance between spiritual and intellectual growth. These findings emphasize the importance of integrating a religion-based curriculum into the educational framework to improve academic success